Study of the antimicrobial activities of the bark extract of cinnamomum verum on multi drug resistant klebsiella pneumoniae and enterobacter agglomerans - Mahmud-Un-Nabi, Mohammad Al (BRAC University, 2015)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2015